C5a contributes to intraocular inflammation by affecting retinal pigment epithelial cells and immune cells. Issue 12 (25th August 2011) - Hu, Mengjun; Liu, Baoying; Jawad, Shayma; Ling, Diamond; Casady, Megan; Wei, Lai; Nussenblatt, Robert B
Abstract : Background: The complement activation molecule C5a has been found in the eye and is implicated in the pathogenesis of ocular inflammatory diseases. In this study, the authors sought to investigate C5a's effects on human retinal pigment epithelial (RPE) cells and peripheral blood mononuclear cells (PBMCs), and on the interaction between RPE cells and PBMCs. Methods: Arising retinal pigment epithelia cell line-19 and PBMCs isolated from healthy donors were used in this study. Western blot, real-time PCR and cell surface receptor staining were used to detect C5a receptor expression. Real-time PCR was used to detect cytokine mRNA expression. A thiazolyl blue tetrazolium bromide assay was used to detect cell viability. Cells were stained with Annexin V and 7-aminoactinomycin D for an apoptosis assay. Cell proliferation was measured using a tritiated thymidine incorporation assay. Results: C5a receptors were present on RPE cells, and receptor expression was increased by pro-inflammatory cytokines. C5a suppressed RPE cells' production of transforming growth factor β2, an important immunosuppressive agent in the eye. In addition, the viability of RPE cells was decreased in the presence of C5a, and this effect was not due to apoptosis. C5a increased proliferation of PBMCs and upregulated their production of pro-inflammatory cytokines. Finally, C5a decreased RPE cells' ability to suppress immune cell proliferation. Conclusion: The results provide a direct link between complement activation and intraocular inflammation. This line of information may help to understand the mechanism of the pathogenesis of intraocular inflammatory diseases. Moreover, the authors show that a close, reciprocal interaction between the innate immune system and the adaptive immune system may be involved in the development of such diseases.